Gossypol acetate: A natural polyphenol derivative with antimicrobial activities against the essential cell division protein FtsZ - Du, Ruo-Lan; Chow, Ho-Yin; Chen, Yu Wei; Chan, Pak-Ho; Daniel, Richard A.; Wong, Kwok-Yin (Frontiers in Microbiology, 2023)
Gossypol is a natural polyphenolic aldehyde, and it has attracted increasing attention as a promising drug against pathogenic bacteria. This study focuses on the antimicrobial properties of gossypol acetate. Gossypol acetate can inhibit the growth of Gram-positive bacteria such as the model organism Bacillus subtilis and the pathogen Staphylococcus aureus (both methicillin-sensitive (MSSA) and methicillin-resistant (MRSA)). In addition, gossypol acetate can also inhibit the growth of Gram-negative bacteria when the outer membrane is permeabilized by Polymyxin B nonapeptide (PMBN). Using a cell biological approach, we show that gossypol acetate affects cell division in bacteria. The effect was traced to a defect in assembly of the cell division FtsZ ring. Biochemical analysis showed that the GTPase activity of FtsZ was inhibited and polymerization of FtsZ was enhanced in vitro. Impaired functions of FtsZ by S2303 are consistent with the block to cell division in the bacteria tested. The binding mode of gossypol acetate in FtsZ is modeled using molecular docking. In summary, the results point to gossypol (S2303) as a promising antimicrobial compound that inhibits cell division by affecting FtsZ polymerization and has potential to be developed into an effective antimicrobial drug by chemical modification to minimize its cytotoxic effects in eukaryotic cells.